Impact of IDH1 Mutation on Long-Term Survival in Patients with Diffuse Glioma - Ochirjav, Enkhee; Baldandorj, Tuul; Choe, Gheeyoung; Enkhbat, Bayarmaa (Central Asian Journal of Medical Sciences, 2019)
Objectives: Diffuse brain gliomas are common primary brain tumor associated with a poor prognosis. In this study, we aimed to determine the impact of IDH1 mutation status on long term survival. Methods: Patients who underwent surgery for diffuse brain glioma were selected. Based on IDH1 mutation status, patients were separated into IDH1 mutant and IDH1 wildtype groups. Results: A total of 124 patients with diffuse brain tumor were included (mean age 39±17, 48.4% male). The frequency of IDH1 mutant and IDH1 wildtype were 56.5% (n=70) and 43.5% (n=54), respectively. During follow-up, 76 patients (61.3%) died and the median follow-up was 8 months (IQR 4; 16). Patients with IDH1 mutant more likely younger (36±16 vs. 43±17, p<.05) and had low grade (grade II) tumor (64.3% vs. 20.4%, p<.001). After adjustment of possible predictors, such age, gender, tumor location and surgical type, IDH1 mutant was an independent predictor of all-cause mortality (HR=0.43, 95% CI 0.26- 0.71, p<.001). Kaplan-Meier estimation showed IDH1 mutant is associated with longer survival compared with IDH1 wildtype in low grade tumor (log rank p<.001). Conclusion: Mutated IDH1 is an independent predictor of all-cause mortality in patients with diffuse brain glioma and resulted in longer survival compared with IDH1 wildtype.